Olukotun Receives ACM-IEEE Award. (Communications of the ACM, 2023)
This article discusses the ACM-IEEE CS Eckert-Mauchly award given to Stanford University professor Kunle Olukotun, the award is co-sponsored by the Association of Computing Machinery and the IEEE Computer Society. Olukotun’s career highlights are briefly discussed including his work with multi-core processors, the Transactional Coherence and Consistency approach to parallel programming, and coarse-grained reconfigurable data-flow.